Fiscal Policy in Colombia : Tapping Its Potential for a More Equitable Society - Moller, Lars Christian (World Bank, Washington, DC, 2012)
Colombia has the seventh highest Gini coefficient of income inequality in the world. The Santos Administration is aware of this challenge and is taking important measures to reduce disparities. The government is also aspiring to join the OECD, which exhibits much lower income disparities, mainly as a result of effective policies of fiscal redistribution. In Colombia, meanwhile, direct taxes, indirect taxes, and monetary transfers hardly dent the high Gini coefficient. To reduce income inequality, Colombian policy makers could consider introducing a more progressive tax-transfer system. This paper ranks alternative inequality-reducing fiscal policy options based on their effectiveness. It argues that there are potentially important redistributive potential gains available from tax reforms if combined with good spending decisions. It presents an illustrative reform package that would be sufficient for Colombia to reach levels of inequality similar to Chile or Costa Rica in a fiscally neutral manner. Nonetheless, further analysis is needed to explore all available policy options and identify those best suited for Colombia.